Pendampingan Belajar Mufrodat dengan Permainan Acak Huruf Hijaiyyah Berbantuan Papan Scrabble pada Santri TPQ Lathiful Amien Kedungrejo - Furoidah, Asni; Illiawati, Illiawati (An-Nuqthah, 2023)
This community service activity was carried out at TPQ Lathiful Amien with the subject being assisted by 13 students. In this service, the researcher used a random hijaiyyah letter game with the help of a modified and developed scrabble board. The purpose of this research is to ignite enthusiasm ad increase the knowledge of TPQ students in learning Arabic, especially mufrodat. In assisting the learning of mufrodat with a game of random hijaiyyah letters with the help of a Scrabble board for the students, the researcher used the PAR (Participatory Action Research) assistance method. The impacts resulting from a random game of hijaiyyah letters with the help of a scrabble board that are applied are as follows: (1) TPQ Lathiful Amien students become enthusiastic about learning Arabic, (2) TPQ Lathiful amien student are able to recognize hijaiyyah letters well through the games that are applied, and (3) TPQ Lathiful Amien student can master the mufradzat given related to the Al Madrasah theme.